LTBP-2 competes with tropoelastin for binding to fibulin-5 and heparin, and is a negative modulator of elastinogenesis - Mohamed Sideek, Mohamed Arshad; Menz, Clementine; Parsi, Mahroo K.; Gibson, Mark A. (Elsevier B.V, 2013)
Latent transforming growth factor-beta-1 binding protein-2 (LTBP-2) is a protein of ill-defined function associated with elastic fibers during elastinogenesis. Although LTBP-2 binds fibrillin-1, fibulin-5, and heparin/heparan sulfate, molecules critical for normal elastic fiber assembly, it does not interact directly with elastin or its precursor, tropoelastin. We investigated the modulating effect of LTBP-2 on two key interactions of tropoelastin during elastinogenesis a) with fibulin-5 and b) with heparan sulfate (using heparin). Firstly, using solid phase assays we showed that LTBP-2 bound fibulin-5 (Kd = 26.47 ± 5.68 nM) with an affinity similar to that of the tropoelastin-fibulin-5 interaction (Kd= 24.66 ± 5.64 nM). Then using a competitive binding assay we showed that LTBP-2 inhibited the tropoelastin-fibulin-5 interaction in a dose dependent manner with almost complete inhibition obtained with 5-fold molar excess of LTBP-2. Interestingly, a fragment of LTBP-2 containing the fibulin-5 binding sequence only partially inhibited the tropoelasin-fibulin-5 interaction suggesting that LTBP-2 was directly blocking only the C-terminal tropoelastin binding site on fibulin-5 and indirectly blocking tropoelastin binding to the N-terminal region. In parallel experiments heparin was shown to have minor inhibitory effects on fibulin-5 interactions with tropoelastin and LTBP-2. However, LTBP-2 was shown to significantly inhibit the binding of heparin to tropoelastin with 50% inhibition achieved with 10 fold molar excess of LTBP-2. Confocal microscopy of fibroblast matrix showed strong co-distribution of LTBP-2 with fibulin-5 and fibrillin-1 and partial co-distribution with heparan sulfate proteoglycans, perlecan and syndecan-4. Also addition of exogenous LTBP-2 to ear cartilage chondrocyte cultures blocked elastinogenesis in a concentration-dependent manner. Overall the results indicate that LTBP-2 may have a negative regulatory role during elastic fiber assembly, perhaps in displacing elastin microassemblies from complexes with fibulin-5 and/or cell surface heparan sulfate proteoglycans.